Strength-Based Parenting as a Predictor of Adolescent Self-Esteem - Agnes Maria Sumargi; Sarah Firlita (Jurnal Sains Psikologi, 2020)
This study aimed to investigate whether strength-based parenting, in particular both aspects of parenting (strength knowledge and strength use), could predict adolescent self-esteem. Participants were 215 adolescents who were studied at a high school in Surabaya. Data were collected using the Rosenberg Self-Esteem Scale to measure self-esteem and the Strength-Based Parenting scale (Strength Knowledge Scale and Strength Use Scale) to measure strength-based parenting. Based on correlation analysis, significant positive relationships were found between strength knowledge and self-esteem, and between strength use and self-esteem. The result of multiple regression analysis revealed that strength knowledge and strength use predicted adolescent self-esteem, but only strength knowledge made a significant unique contribution to adolescent self-esteem.Keywords: self-esteem; adolescents; strength-based parenting.